2022
DOI: 10.3390/children9070952
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence on Pulmonary Function after Asymptomatic and Mild COVID-19 in Children

Abstract: Background: While it has been described that adults can develop long-lasting deterioration in pulmonary function (PF) after coronavirus disease 19 (COVID-19), regardless of disease severity, data on the long-term pneumological impact of SARS-CoV-2 infection in children are lacking. Methods: Performing a single-center, prospective, observational study on children aged 6–18 years with a previous diagnosis of asymptomatic/mild COVID-19, we evaluated the long-term impact of mild severe acute respiratory syndrome c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Some studies were excluded because of duplication. Finally, seven articles including 345 patients were enrolled in the present review (13)(14)(15)(16)(17)(18). Eligible studies were including 5 cross sectionals (13,14,16,17,19) and 2 longitudinal studies (15,18).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies were excluded because of duplication. Finally, seven articles including 345 patients were enrolled in the present review (13)(14)(15)(16)(17)(18). Eligible studies were including 5 cross sectionals (13,14,16,17,19) and 2 longitudinal studies (15,18).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, seven articles including 345 patients were enrolled in the present review (13)(14)(15)(16)(17)(18). Eligible studies were including 5 cross sectionals (13,14,16,17,19) and 2 longitudinal studies (15,18). In one study the z score of spirometry parameters were reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations